Misuse of institutions: Lessons from Transition - Leonid Polishchuk (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper explores a phenomenon often observed in transition economies, when newly established institutions are misused, i.e., applied or resorted to for reasons which have little in common with their intended or anticipated purpose. In such incidences institutions become sources of private gains and lose their value-creation role and capacity. We offer a typology of institutional misuse (illustrated by examples from Russian transition), discuss its consequences, and explore reasons why governments and societies fail to serve as institutions' guardians. Implications misused institutions for economic and political reforms are analysed.
Keywords: D02; D72; D78; 330; institutions; transition; capture; club goods